A rat tail temporary static compression model reproduces different stages of intervertebral disc degeneration with decreased notochordal cell phenotype. Issue 3 (28th November 2013) - Hirata, Hiroaki; Yurube, Takashi; Kakutani, Kenichiro; Maeno, Koichiro; Takada, Toru; Yamamoto, Junya; Kurakawa, Takuto; Akisue, Toshihiro; Kuroda, Ryosuke; Kurosaka, Masahiro; Nishida, Kotaro
ABSTRACT The intervertebral disc nucleus pulposus (NP) has two phenotypically distinct cell types—notochordal cells (NCs) and non‐notochordal chondrocyte‐like cells. In human discs, NCs are lost during adolescence, which is also when discs begin to show degenerative signs. However, little evidence exists regarding the link between NC disappearance and the pathogenesis of disc degeneration. To clarify this, a rat tail disc degeneration model induced by static compression at 1.3 MPa for 0, 1, or 7 days was designed and assessed for up to 56 postoperative days. Radiography, MRI, and histomorphology showed degenerative disc findings in response to the compression period. Immunofluorescence displayed that the number of DAPI‐positive NP cells decreased with compression; particularly, the decrease was notable in larger, vacuolated, cytokeratin‐8‐ and galectin‐3‐co‐positive cells, identified as NCs. The proportion of TUNEL‐positive cells, which predominantly comprised non‐NCs, increased with compression. Quantitative PCR demonstrated isolated mRNA up‐regulation of ADAMTS‐5 in the 1‐day loaded group and MMP‐3 in the 7‐day loaded group. Aggrecan‐1 and collagen type 2α‐1 mRNA levels were down‐regulated in both groups. This rat tail temporary static compression model, which exhibits decreased NC phenotype, increased apoptotic cell death, and imbalanced catabolic and anabolic gene expression, reproduces different stages of intervertebral disc degeneration. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:455–463, 2014.